Empathy: Superpower Tersembunyi Bagi Gen Z untuk Menembus Gerbang Dunia Kerja - Diana Zumrotus Sa’adah; Nanda Puspitasari; Dewi Khayyirah Novrianti; M. Abdullah Azzam; Radiah Azzahrah; Wisma Niha (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
Generation Z is entering an increasingly dynamic and competitive workforce, where technical skills alone are no longer sufficient for achieving success. Social and emotional skills, particularly empathy, have become key to building effective and sustainable relationships. This article presents a literature review exploring empathy as a “hidden superpower” for Gen Z to navigate the gateway to the professional world. The research method employed is a systematic literature study, analyzing scholarly articles, journals, and recent publications related to empathy, leadership, emotional intelligence, and multigenerational interactions in the workplace. The analysis indicates that empathy strengthens interpersonal relationships, fosters trust, and supports effective communication, while also enhancing leadership effectiveness, emotional intelligence development, and organizational sustainability. Empathetic Gen Z individuals are better equipped to navigate cross-cultural interactions, handle work pressure, and balance digital and emotional intelligence, making it a unique social and competitive capital. These findings highlight the importance of developing empathy as a strategic competency in education and soft skills training to support career success and organizational resilience in the global work era.